1999
DOI: 10.1073/pnas.96.5.2153
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and elasticity of the fibronectin matrix in living cell culture visualized by fibronectin–green fluorescent protein

Abstract: Fibronectin (FN) forms the primitive fibrillar matrix in both embryos and healing wounds. To study the matrix in living cell cultures, we have constructed a cell line that secretes FN molecules chimeric with green f luorescent protein. These FN-green f luorescent protein molecules were assembled into a typical matrix that was easily visualized by f luorescence over periods of several hours. FN fibrils remained mostly straight, and they were seen to extend and contract to accommodate movements of the cells, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
189
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(205 citation statements)
references
References 26 publications
12
189
0
4
Order By: Relevance
“…Proteins such as titan and tenascin have been unfolded by using atomic force microscopy and optical tweezers (18,19), but the question of whether cells unfold proteins or protein modules under physiological conditions remains unanswered (14,20). By measuring FRET between donor and acceptor f luorophores conjugated to Fn, we were able to investigate the effect of cell-generated tension on the structure of Fn in fibrillar matrices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins such as titan and tenascin have been unfolded by using atomic force microscopy and optical tweezers (18,19), but the question of whether cells unfold proteins or protein modules under physiological conditions remains unanswered (14,20). By measuring FRET between donor and acceptor f luorophores conjugated to Fn, we were able to investigate the effect of cell-generated tension on the structure of Fn in fibrillar matrices.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution structures of FnIII modules have shown that different modules are structurally homologous and measure 3.2 nm from N to C terminus (22)(23)(24)(25). Because FRET is limited to donors and acceptors located within 10 nm of each other (26), only donors within modules FnIII 5-9 and FnIII [13][14][15] are sufficiently close to acceptors located within FnIII 7 and FnIII 15 to permit energy transfer. From 2 M to 4 M Gdn⅐HCl, FnIII modules unfold sequentially, beginning with the least stable modules (16,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently believed that Fn fibers can be stretched three-to four-fold beyond their resting length (Ohashi et al, 1999). This conclusion was derived from various cell culture measurements of the lengths of chimeric GFP or YFP-Fn fibers before and after breakage or detachment of fibers under cell-dependent strain, from fiber rupture from laser damage, or after inhibition of cell contractility with cyto-chalasin B.…”
Section: Fn Fibers Show Signs Of Breakage Only When Stretched Over 5-mentioning
confidence: 99%
“…The conformations Fn assumes on synthetic surfaces, however, are rather distinct from those of native Fn in soluble and fibrillar forms (reviewed in Antia et al, 2006;Baugh and Vogel, 2004;Halter et al, 2005). Fn polymerization into fibers is thought to proceed as cryptic self-assembly sites are exposed by cell contractility (Baneyx and Vogel, 1999;Mao and Schwarzbauer, 2005;Ohashi et al, 1999;Zhong et al, 1998).…”
Section: Introductionmentioning
confidence: 99%